The Foundry: the DNA synthesis and construction Foundry at Imperial College. (9th June 2016) - Chambers, Stephen; Kitney, Richard; Freemont, Paul
Abstract : The establishment of a DNA synthesis and construction foundry at Imperial College in London heralds a new chapter in the development of synthetic biology to meet new global challenges. The Foundry employs the latest technology to make the process of engineering biology easier, faster and scalable. The integration of advanced software, automation and analytics allows the rapid design, build and testing of engineered organisms.